Museum-Body-Device: a Semiotic Study of Visits to the Centre Pompidou - Rosso , Aluminé (E|C, 2023)
This article analyzes how the materialities involved in modern art museums establish different links between the institutions and their public. Through the semio-anthropological perspective developed by Traversa (2009, 2014) and Verón (1983, 2013), this research examines the new types of links that emerge from the intersection, tension, or overlapping of the different material supports (physical and virtual) that manage the development of the museum visit. Observing these links is possible by analyzing the different enunciative scenes configured by the institutional discourse according to its orientation towards the different types of collectives that coexist in the contemporary museum experience: audiences, followers, and visitors. The case of the analysis presented is the communicative device of the Pompidou Center (Paris): website, profiles on social networks, spatial organization, and, particularly, the application “Suivez le guide” since this is presented as a tool of mediation between the physical and virtual instances of the museum experience, what we have called mediated visit and mediatized visit.